Respuesta agronómica del cultivo de amaranto (amaranthus spp) a La aplicación de dos bioestimulantes orgánicos. - Ramírez Guaita, Jhomara Elizabeth (2020)
The present investigation was carried out in the Sacha Wiwa Research Center, of the Guasaganda Parish belonging to the La Maná Canton, with the objective of evaluating the agronomic response of the Amaranth crop (Amaranthus spp) with the use of two organic biostimulants in different dose, for which a Random Complete Blocks Design with factorial arrangement 3x2x3 + 3 was used; where A are the varieties of amaranth, San Pedro (A. hypochondriacus), Sangorache (A. quitensis) and Valentina (A. tricolor), B are the biostimulants based on seaweed and amino acids, C the doses of 2, 4 and 6 ml / liter and 3 absolute controls per variety, so the investigation consists of 21 treatments with three repetitions. In the phenological state of the crop, measurements were made in growth variables such as: emergency percentage, stem length (cm), number of leaves, in terms of agronomic variables, the days of flowering were evaluated, while in the productive variables the number of panicles and productive branches, to determine the effect produced by biostimulants on the crop. The evaluation was carried out at 30, 45, 60 and 75 days, obtaining as final results: percentage of germination, in stem length (cm), number of leaves, days to flowering, productive branches and number of panicles, in the days at flowering the varieties bloomed at 65, 100 and 105 days; the emergency percentage was 95%, in the length of the stem the T5 (V1B2D2) reached the highest average with 62.43 cm at 75 days, in the number of leaves the T5 (V1B2D2) obtained an average of 34.68 at 75 days, in the productive branches the T15 (V3B1D3) achieved an average of 12.49 at 110 days, while in the number of panicles at 120 days the T15 (V3B2D3) reached an average of 12.59 respectively.